Innovations in Culture and Development - Jelinčić, Daniela Angelina. author. aut Link
XXIII, 112 p. 3 illus.
Keywords: This book focuses on innovations in culture having the potential to drive overall development. It analyses public policies and offers inspiring examples of innovations in culture which solve various societal problems as well as recommendations for public policies. The “culturinno effect” (culture + innovations), thus presents evidence of the inherent power culture has in fostering development. The volume leads us through the role of culture in different concepts of development, providing the theoretical and historical context of development and theory of change. Analysis of theoretical cultural policy models is followed by practical examples of innovations in culture, culminating in a text that is a must have for innovative decision makers ready to respond to the challenges of today as well as students, artists and cultural workers who are prepared to offer a new view on arts/culture. .